Analysis of the Role of Vitamin C Hypovitaminosis in Scurvy on Bone Health: A Single Center Observational Study at Dr. Moewardi General Hospital, Surakarta, Indonesia - Nefihancoro, Udi Heru; Rachmad Faisal (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Scurvy, vitamin C deficiency, is a rare condition but remains relevant in Indonesia. This study aims to analyze the role of vitamin C hypovitaminosis in the development of scurvy and its impact on bone health through an observational study at Dr. Moewardi General Hospital. Surakarta. Methods: A cross-sectional observational study was conducted on 30 patients diagnosed with scurvy at Dr. Moewardi General Hospital Surakarta during the 2020-2023 period. Demographic data, medical history, nutritional status, and severity of scurvy were collected. A radiological examination of the bone is performed to assess scurvy-related changes. Descriptive, comparative, and Spearman correlation statistical analyzes were used. Results: The majority of patients were men (66.7%) with a mean age of 45 years. A history of an unbalanced diet with low fruit and vegetable intake was found in the majority of patients (86.7%). Common symptoms include fatigue (86.7%), joint pain (73.3%), bleeding gums (60%), and skin bleeding (53.3%). The severity of scurvy varied, with 10 patients (33.3%) experiencing severe scurvy. Radiological examination shows significant changes in long bones, especially osteoporosis and thinning of the cortex, which is more obvious in patients with severe scurvy. Spearman correlation analysis showed a positive correlation between the severity of scurvy and the incidence of osteoporosis (rho = 0.495, p = 0.005) and cortical thinning (rho = 0.394, p = 0.031). Conclusion: Vitamin C hypovitaminosis plays a significant role in the development of scurvy and has a negative impact on bone health. Early screening and diagnosis of scurvy are important to prevent musculoskeletal complications. Nutritional education and dietary interventions to increase vitamin C intake need to be intensified, especially in high-risk groups.